Metal, nutrient and biomass accumulation during the growing cycle of Miscanthus established on metal‐contaminated soils. Issue 2 (12th February 2016) - Nsanganwimana, Florien; Waterlot, Christophe; Louvel, Brice; Pourrut, Bertrand; Douay, Francis
Abstract: The energy crop Miscanthus presents high potentials for phytomanagement. Its shoot yield and nutrient accumulation has been extensively characterized in uncontaminated agricultural soils, while very little is known for metal‐contaminated conditions. This study aimed at assessing potential differences in dry matter and metal and nutrient accumulation of the standing aerial biomass in Miscanthus ( M. × giganteus ) growing in situ on agricultural plots presenting different soil Cd, Pb, and Zn concentrations. Plant samplings were conducted monthly along the growing period from May to December. Cadmium, Pb, Zn, and the concentrations of the nutrients N, P, K, Ca, Mg, and Na were determined in leaves and stems separately. During the growing phase, the maximum dry matter was reached in early in autumn. Whatever the organ, Cd and Zn concentrations were higher on contaminated than on uncontaminated plots. During summer and autumn, Zn and Pb concentrations were higher in leaves than in stems whereas Cd concentrations did not significantly differ between the organs. Concentrations of N, P, K, and Mg decreased across the study period whereas those of Ca and Na increased. Overall, metal and nutrient concentrations depended on plant organ and its development stage. The dry matter and nutrient accumulation patterns were not different between contaminated and uncontaminated plots. The significance of these findings is discussed in light of best phytomanagement practices and potential uses of Miscanthus biomass.